Population Dynamics of Tilapia (Oreochromis niloticus) in the waters of Tempe Lake, Wajo Regency, South Sulawesi - Amir, Faisal; Mallawa, Achmar; Fahrul, Fahrul; Farhum, St. Aisyah; Purnamawati, Hanifa (Fakultas Pertanian, Universitas Muhammadiyah Maluku Utara, 2023)
This study aims to analyze the tilapia population parameters in the waters of Lake Tempe, including estimating population parameters, as well as catches per recruit. Data on body length measurements (Lt, cm) of tilapia caught by monofilament gill net and bottom trap in October â€“ December 2021 amounted to 1600 individuals. The tilapia growth model follows the von Bertalanffy growth model. Pauly's empirical formula and the catch curve are used to estimate the M and total mortality (Z), respectively. The fishing mortality rate (F) is obtained by F=Z-M. The value â€œEâ€ is obtained from E=F/Z; (Y/R)' values using the Beverton and Holdâ€™s formulas. FISAT-II software was used to calculate all parameters of Oreochromis niloticus population dynamics. The research results show that the estimated values for growth parameters (Lâˆž, K, and t0) of tilapia are 35.5 cm; 0.35 per year; and -0.4512 years. The estimated of natural mortality, total mortality, fishing mortality, and exploitasi rate are 0.89 year-1 each; 2.68 years-1, 1.79 years; and 0.7. Mean while, the estimated actual Y/R' and optimal Y/R' values are 0.013 g/recruitment and 0.0155 g/recruitment, respectively. In conclusion, the tilapia in Lake Tempe takes a long time to reach its maximum length. Greater mortality is caused by arrest factors. The status of the tilapia fishery is over-exploited, in conditions where the optimal Y/R' value is higher than the actual Y/R'.